1997
DOI: 10.1046/j.1471-4159.1997.69010021.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wild‐Type and Mutated Copper/Zinc Superoxide Dismutase on Neuronal Survival and l‐DOPA‐Induced Toxicity in Postnatal Midbrain Culture

Abstract: • Abstract: Mutations in the free radical-scavenging enzyme copper/zinc superoxide dismutase (Cu/Zn-SOD) are associated with neuronal death in humans and mice. Here, we examine the effects of human wild-type (WT SOD) and mutant (Gly 93 -÷ Ala; G93A) Cu/Zn-SOD enzyme on the fate of postnatal midbrain neurons. Oneweek-old cultures from transgenic mice expressing WT SOD enzyme had significantly more midbrain neurons and fewer necrotic and apoptotic neurons than nontransgenic cultures. In contrast, 1-week-old cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 34 publications
(29 reference statements)
5
31
0
Order By: Relevance
“…Similar observations were subsequently made in transfected PC-12 cells (29) and in primary neurons grown from transgenic mice expressing mutant SOD1 (30). Collectively, these in vitro data have led many investigators to consider that mutant SOD1 may kill motor neurons by activating PCD, a term that we here use in the sense of cell death mediated by specific signaling pathways.…”
Section: Hypothesis For Mutant Sod1 Cytotoxicitysupporting
confidence: 63%
“…Similar observations were subsequently made in transfected PC-12 cells (29) and in primary neurons grown from transgenic mice expressing mutant SOD1 (30). Collectively, these in vitro data have led many investigators to consider that mutant SOD1 may kill motor neurons by activating PCD, a term that we here use in the sense of cell death mediated by specific signaling pathways.…”
Section: Hypothesis For Mutant Sod1 Cytotoxicitysupporting
confidence: 63%
“…Both neuronal populations had native cytosolic dopamine levels beneath the detection limit of the technique (<100 nM). Exposure to l-DOPA at 100 μM, a level that produces cytosolic dopaminochrome and neuromelanin (33) and eventually kills dopaminergic neurons but not the GABAergic neurons (34), increased cytosolic dopamine in unlabeled, predominantly GABAergic neurons to 2.5 ± 0.6 μM (n = 20), while in dopaminergic neurons, free cytosolic dopamine reached 17.7 ± 2.7 μM (n = 34, P < 0.001); thus, the level of dopamine reached in the neuronal cytosol was nearly identical to the dopamine concentration used to produce the DA-α-syn in vitro (14 μM).…”
Section: Resultsmentioning
confidence: 99%
“…The cultures were incubated with 100 μM l-DOPA for 1 hour prior to and during the recordings. After background current subtraction, dopamine concentration at the pipette tip was calculated using calibration curves generated for carbon fiber electrodes with different exposed surfaces (34). The initial concentration of cytosolic dopamine was calculated using the neuronal cell body volume and the volume of the pipette tip estimated from photographs acquired before each recording.…”
Section: Intracellular Patch Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on cell survival by Bcl-2 have reported using cell lines transfected with mutant SOD1 cDNA, 31,32 and a few using primary neuronal cultures. 33 In our experiment, we used primary neuronal cells with SOD1 mutation separated from wildtype neuronal cells. We wanted to compare the difference between primary neuronal cells with SOD1 mutation and those with the wild-type in protection by overexpression of Bcl-2 using various apoptotic stimuli and conditions.…”
Section: Figure 7 Detection Of Immunoreactivity For Bcl-2 In the Tongmentioning
confidence: 99%